Behavioral changes in gym attending due to COVID-19 pandemic: A descriptive survey - Almasri, D.; Noor, A.; Diri, R. (Journal of Microscopy and Ultrastructure, 2020)
Introduction: On the declaration of the COVID-19 pandemic lockdown clearance in Saudi Arabia, the high-profile precautions were applied as a major step to resume the normal life activities and to coexist with the pandemic. One of those resumed activities is the reopening of the gym and fitness centers. The perception and the commitment with safe precautions in terms of personal hygiene and sterilization have dramatically changed due to the COVID-19 pandemic. The purpose of this study was to assess the behavior of gym attendees toward preventive precautions prior to the pandemic and the behavioral changes that will be accommodated after the new policy and procedure of attending a gym and fitness centers. Methods: A cross-sectional descriptive study was conducted in February 2020, a 1 month prior to the complete lockdown announcement in Saudi Arabia as a result of the COVID-19 pandemic outbreak. An electronic questionnaire was provided during a personal interview with gym and fitness centers' participants. Results: The majority of participants never use sterile wipes or any sterile product before or after using gym equipment (61.6%), and 35.4% of gym attendants do not use any sterilization materials distributed through fitness centers. In addition, most of the participants have had an episode of skin infections or respiratory infection at the fitness center for the past 12 months (22.2%), whereas 80.8% do not know about tinea microbial that causes athlete's foot, and 65.7% of them utilize the shower in the gym after their workout. Conclusion: The lack of awareness of previous and new gym members regarding safety precautions during indoor exercise should be overcome by more future educational intervention and emphasizing on following the Ministry of Sports in Saudi Arabia, even after the complete clearance of COVID-19 pandemic.